Pencegahan COVID-19 Pada Balita Dengan Pelatihan Cuci Tangan Dan Pemakaian Masker - Saputri, Romadhiyana Kisno; Musyafa’ah, Nurul; Izza, Yogi Prana; Nisa’, Shofi Chofiatun; Inayah, Nurin (Universitas Islam Nahdlatul Ulama Jepara, 2023)
In Bojonegoro, the death rate due to COVID-19 is relatively high. In February 2022, the total confirmed cases of COVID-19 in Bojonegoro were 1337 cases with about 24% of cases or 321 cases in Kapas District. Children under 5 years old or toddlers have a great potential for transmission of COVID-19, especially toddlers who are not the target of vaccination. Prevention of transmission of COVID-19 to toddlers can be done by disciplining toddlers to wash their hands with soap and wear masks. This community service activity aims to make efforts to prevent COVID-19 in toddlers by hand washing training and wearing masks correctly. The method of community service is carried out by means of lectures and demonstrations. Community service activities are said to be successful because they increase the knowledge and skills of 86.11% of targets related to how to wash hands as recommended and increase the knowledge and skills of 100% of targets related to the use of masks according to the recommendations. All targets have been proven to be disciplined to wash their hands when they want to eat and enter the house and use masks when leaving the house.